Taking a Text and Tweaking it : Using Wendy Belcher's 12-Week Journal Writing Program to Support Writing Wellbeing for Busy Educators. - Winter, Abigail (Student Success v.14 n.3 p.120-127 https://doi.org/10.5204/ssj.2764, 2023)
This practice report argues that, in a higher education system where publication is a key performance metric, existing resources, such as textbooks, can be used and modified to make engaging and valuable professional development resources for researcher/educators - both students and academics. The report outlines a series of writing workshops offered over 2021 and 2022 at Queensland University of Technology, based on Wendy Laura Belcher's 2019 book Writing Your Journal Article in Twelve Weeks: A Guide to Academic Publishing Success. The practice report describes the specific steps taken to "tweak", or re-work the book-as-curriculum, to provide flexibility and a place for writing wellness for educators during over-crowded academic semesters. It also provides a case study of the usefulness of the writing program for educators in enhancing their writing wellbeing, and ends with lessons for other academic developers who may be considering using existing texts as the basis for professional development for already-overworked staff in the neoliberal academy. [Author abstract]